2010
DOI: 10.1080/14786410802529190
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial, antifungal and antioxidant activities of the flower oil ofRetama raetam(Forssk.) Webb from Tunisia

Abstract: The chemical composition of the essential oils obtained by hydrodistillation from the flowers of Retama raetam (Forssk.) Webb cultivated in Tunisia was determined by GC and GC/MS analysis. A total of 50 components representing 98.58% of the oil were identified: nonanal (35.75%), alpha-humulene (29.29%), acetaldehyde (7.84%), linalool (5,62%), myrcene (3.38%), tridecanal (2.21%), beta-caryophyllene (1.79%), alpha-terpinyl acetate (1.46%), terpinolene (1.26%) and methyl anthranilate (1.06%) were found to be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 11 publications
1
31
0
1
Order By: Relevance
“…The crude plant extracts of R. raetem and H. scoparia were exhibited significant reduction in the growth of four fungi which was in parallel with pervious study [48] (Figure 8(a)). It has been reported that raetem extract showed an antibacterial, antifungal and anticancer activity [56].…”
Section: Antimicrobial and Antifungal Activitiessupporting
confidence: 74%
See 1 more Smart Citation
“…The crude plant extracts of R. raetem and H. scoparia were exhibited significant reduction in the growth of four fungi which was in parallel with pervious study [48] (Figure 8(a)). It has been reported that raetem extract showed an antibacterial, antifungal and anticancer activity [56].…”
Section: Antimicrobial and Antifungal Activitiessupporting
confidence: 74%
“…This expectation that some naturally occurring plant ingredients can kill antibioticresistant strains of bacteria such as Bacillus cereus, Escherichia coli, Micrococcus luteus and Staphylococcus aureus has been confirmed [48].…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 92%
“…Webb., qui pousse au Maroc dans les régions désertiques (Tafilalt) et le Moyen Atlas est essentiellement recommandée par les guérisseurs traditionnels [7,8] comme antidiabétique. En outre, il a été rapporté que ces espèces possèdent divers effets pharmacologiques associés entre autres à la présence des quinolizidines : effets hypoglycémique, diuré-tique [9][10][11], cytotoxique [12][13][14][15][16], antihypertenseur [17], antibactérien [18][19][20], antifongique, antiviral [18,21,22] et antioxydant [19,22].…”
Section: Introductionunclassified
“…Martins et al (2014) suggested that the observed b-carotene antioxidant capacity in the Schinus molle L. (Anacardiaceae) EO can be justified by the presence of the monoterpenes. Edziri et al (2010) reported that Retama raetam (Forssk.) Webb (Fabaceae) EO has a good AA (measured through the DPPH method), and they consider that this activity could be attributed to the relatively high percentage of monoterpenes present in the oil.…”
Section: Antioxidant Activity Versus Phytochemical Compositionmentioning
confidence: 99%